Prognostic factors and adjuvant therapy on survival in early-stage cervical adenocarcinoma/adenosquamous carcinoma after primary radical surgery: A Taiwanese Gynecologic Oncology Group (TGOG) study. (September 2016) - Twu, Nae-Fang; Ou, Yu-Che; Liao, Cheng-I.; Chang, Wei-Yang; Yang, Lan-Yan; Tang, Yun-Hsin; Chen, Tze-Chien; Chen, Chi-Hau; Chen, Tze-Ho; Yeh, Lain-Shung; Hsu, Shih-Tien; Chen, Yu-Chieh; et al.
Abstract: Objective: We aimed to identify prognostic factors of early-stage cervical adenocarcinoma (AC) and adenosquamous carcinoma (ASC) treated with primary radical surgery, and to evaluate the impact of postoperative adjuvant therapy on outcome. Methods: The clinical-pathological data of all patients (n = 1132) with stages I-II cervical AC/ASC treated with primary radical surgery at the member hospitals of the Taiwanese Gynecologic Oncology Group were retrospectively reviewed. Results: In multivariate analysis, stage II, deep stromal invasion (DSI), lymphovascular space invasion (LVSI), positive pelvic lymph node (PLN), and parametrial involvement (PI) were significant factors for recurrence-free survival (RFS), while only DSI, PI, and positive PLN were independent factors for cancer-specific survival (CSS). Low- and high-risk groups were defined by prognostic scores derived from the four factors (DSI, LVSI, positive PLN, PI) selected by internal validation. Postoperative adjuvant therapy significantly improved outcome for PLN-positive patients (RFS, p  = 0.014; CSS, p  = 0.016), but not for PLN-negative high-risk group because of higher mean prognostic score ( p  = 0.028) of adjuvant+ than adjuvant− patients. Conclusions: PLN metastasis, PI, DSI, and LVSI were independent prognostic factors. Prospective studies of postoperative adjuvant therapy with prognostic score and nodal status stratification for cervical AC/ASC are necessary. Highlights: Stage, pelvic node metastasis, parametrial involvement, DSI, and LVSI were independent prognostic factors for cervical adeno-adenosquamous carcinoma. Adjuvant therapy after radical surgery significantly improved survival for node-positive but not for node-negative high-risk group. Prospective studies with prognostic score and nodal status stratification for high-risk cervical adeno-adenosquamous carcinoma are necessary.